HVS Based Face Recognition Using Slant Transform - Veearaswamy, K; Koteswara Rao, M; Anithasheela, K; Himabindu, Ch (International Journal of Engineering and Technology, 2018)
There are many person identification technologies like password, PIN, key, and token are used in many applications. Present, popular identification technology is face. In many applications the database is large. Hence, recognition with high speed is major challenge. This paper presents a recognition using HVS features in transform domain. Human visual system identifies perceptual important information in the images. Slant transform basis vector is sawtooth. It efficiently represents linear brightness variations along an image line. Hence, in this work HVS features in slant transform domain is explored for face recognition. Feature vector is based on HVS parameters. In this method image is decomposed into subblocks using Slant Transform. Important elements are identified using HVS weightage. Experiments are performed on bench mark face databases. Proposed method has better recognition performance than existing methods. Retrieval time is also less.Â Â